1983
DOI: 10.1016/s0072-968x(83)80018-7
|View full text |Cite
|
Sign up to set email alerts
|

The Fate of Injected Trigger Fingers

Abstract: Patients who were scheduled for surgical release of their trigger fingers underwent an injection of the involved tendon sheath prior to surgery. In thirty-six patients the injection of methylene blue was undertaken in a proximal-distal direction and in forty-three the direction of the injection was reversed. The success rate of the injections was 61 per cent. in the proximal distal group and 37 per cent in the second group. There was no significant statistical difference with regard to age, but duration of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0

Year Published

1988
1988
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(12 citation statements)
references
References 2 publications
0
12
0
Order By: Relevance
“…w9 Injecting into the flexor sheath can prove difficult, as shown by Kamhin et al, who injected trigger fingers with dye and then went on to do an open A1 pulley release. They noted that only half of the injected fingers had dye within the sheath and that failure to introduce dye into the flexor sheath was higher in those patients with a longer duration of symptoms 19. Complications include dermal or subcutaneous atrophy, skin hypopigmentation, infection, and in one rare case tendon rupture.…”
Section: Treatmentmentioning
confidence: 99%
“…w9 Injecting into the flexor sheath can prove difficult, as shown by Kamhin et al, who injected trigger fingers with dye and then went on to do an open A1 pulley release. They noted that only half of the injected fingers had dye within the sheath and that failure to introduce dye into the flexor sheath was higher in those patients with a longer duration of symptoms 19. Complications include dermal or subcutaneous atrophy, skin hypopigmentation, infection, and in one rare case tendon rupture.…”
Section: Treatmentmentioning
confidence: 99%
“…description of the location of injected material, Kamhin et al 11 reported that 49% of material ended up inside the tendon sheath, and the remaining 51% was located in the surrounding soft tissue. Because this previous work was a clinical study, it did not determine whether any material ended up inside the tendon, an outcome that would likely lead to severe complications.…”
mentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11] However, overall results with nonoperative management have been variable and disappointing. [12][13][14] Operative treatment requires an incisional release of the A1 pulley. [15][16][17][18][19][20][21] Success rates are higher with surgical treatment, but so are complication rates.…”
mentioning
confidence: 99%